2003
DOI: 10.1029/2003jd003440
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric response to solar radiation absorbed by phytoplankton

Abstract: [1] Phytoplankton alter the absorption of solar radiation, affecting upper ocean temperature and circulation. These changes, in turn, influence the atmosphere through modification of the sea surface temperature (SST). To investigate the effects of the present-day phytoplankton concentration on the atmosphere, an atmospheric general circulation model was forced by SST changes due to phytoplankton. The modified SST was obtained from ocean general circulation model runs with space-and time-varying phytoplankton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 25 publications
5
40
6
Order By: Relevance
“…Zhai et al (2011) demonstrated increased heat loss from the ocean to the air associated with bio-optical heating of the upper ocean caused by the presence of phytoplankton in the Gulf of St. Lawrence. Atmospheric heat gain induced by the presence of phytoplankton has been further examined in coupled ocean-atmosphere models, which show an amplification of the seasonal cycle of temperature in the troposphere, modulating the tropical convection patterns and atmospheric circulation (Shell et al 2003) and affecting large patterns of climate variability such as ENSO (Zhang 2015).…”
Section: Effect Of Eddiesmentioning
confidence: 99%
“…Zhai et al (2011) demonstrated increased heat loss from the ocean to the air associated with bio-optical heating of the upper ocean caused by the presence of phytoplankton in the Gulf of St. Lawrence. Atmospheric heat gain induced by the presence of phytoplankton has been further examined in coupled ocean-atmosphere models, which show an amplification of the seasonal cycle of temperature in the troposphere, modulating the tropical convection patterns and atmospheric circulation (Shell et al 2003) and affecting large patterns of climate variability such as ENSO (Zhang 2015).…”
Section: Effect Of Eddiesmentioning
confidence: 99%
“…Not surprisingly, since visible light inhabits a substantial portion of the shortwave spectrum, Correspondence to: W. Anderson (whit.anderson@noaa.gov) these constituents are important in determining the characteristic hue of seawater, often termed ocean color. Several bodies of work have investigated or suggested the importance of ocean color on the circulation of the ocean and the climate system (Rosati and Miyakoda, 1988;Lewis et al, 1990;Stramska and Dickey, 1993;Schneider and Zhu, 1998;Nakamoto et al, 2001;Murtugudde et al, 2002;Timmerman and Jin, 2002;Shell et al, 2003;Sweeney et al, 2005;Manizza et al, 2005;Lengaigne et al, 2007). Changes in shortwave absorption have also been found to impact interannual tropical variability, both in hybrid coupled models (Marzeion et al, 2005;Ballabrera-Poy et al, 2007) and fully coupled climate models (Lengaigne et al, 2007;Anderson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A global ocean GCM is applied by Manizza et al (2005) to look at the bio-optical feedbacks between phytoplankton, ocean dynamics and sea ice. Possible atmospheric responses are discussed in Shell et al (2003). They first run an ocean GCM to obtain the biologically induced modifications of the sea surface temperature (SST) and then run a global atmospheric simulation using the modified SST.…”
Section: Introductionmentioning
confidence: 99%